Sex and Gender Disparities in Missed Acute Ischemic Stroke: A Nested Case-Control Study - Cécile Barras; Michael Amiguet; Joëlle Schwarz; Patrik Michel; Carole Clair (Clinical and Translational Neuroscience)
Backround: The aim is to analyze whether sex and gender are associated with missed acute ischemic stroke (M-AIS). Methods: We performed a nested case-control study, using data collected from March 2003 to December 2020 from ASTRAL (Acute STroke Registry and Analysis of Lausanne). M-AIS were compared with a randomly selected control sample of acute ischmemic stroke (AIS). We extracted six gender-related socioeconomic variables. A gendered socioeconomic position (SEP) score was constructed reflecting the level of correspondence with feminine characteristics. Associations between M-AIS and the gender-related socioeconomic variables and the gendered SEP score were investigated using logistic regression. Results: Of the 6007 AIS, 182 (3%) were M-AIS. 80 (44%) were women. No association between administrative sex and M-AIS was found (OR 1.25, 95% CI 0.78–2.00). Differences were found for gender-related socioeconomic variables, women in the middle professional category had higher odds of an M-AIS compared to women in the lower professional category (OR 3.93, 95% CI 1.19–13.03). Men with higher education had lower odds of an M-AIS compared to men with lower education (OR 0.31, 95% CI 0.10–0.92). For women, a 20-unit increase in the gendered SEP score was associated with lower odds of an M-AIS (OR 0.66, 95% CI 0.46–0.94). For men, the same increase in the score tended to higher the odds of an M-AIS (OR 1.52, 95% CI 1.00–2.32). Conclusions: The interaction of administrative sex with gender-related socioeconomic variables revealed different associations with M-AIS for women and men. Correspondence to expected gender norms may have a protective effect against M-AIS.